Styloidectomy: our experience with intraoral approach - Maradesha, Purigali S.; Chandrashekhar, Subash; Jayaramaiah, Samatha K. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Eagle’s syndrome is a symptom complex arising due to elongated styloid process or calcification of stylohyoid ligament. Surgical treatment is regarded as the foremost option. The study aims to put forth our experience with intraoral approach to styloidectomy in 17 subjects. Methods: A retrospective study was conducted between January 2017 to December 2019. The study included 17 subjects with a diagnosis of elongated styloid process. All the subjects underwent styloidectomy by intraoral approach and were followed up. Results: In our study, the median age of the study group was 33.76 and out of 17 subjects 13 were female and 4 male. The procedure was done under local anesthesia in 13 subjects and under general anesthesia in 4 subjects. Styloidectomy by intraoral approach was done in all subjects among which 15 were bilateral and 2 unilateral. 88% of the subjects were symptom free by third week. Conclusions: The study suggests that styloidectomy by intraoral approach is minimally invasive and can be done under local anesthesia with an added advantage of quick recovery.